Metal-Semiconductor-Insulator-Metal Structure Field-Effect Transistors Based on Zinc Oxides and Doped Ferroelectric Thin Films. Issue 1633 (2014) - Jia, Ze; Xu, Jianlong; Wu, Xiao; Zhang, Mingming; Zhang, Naiwen; Liu, Jizhi; Liu, Zhiwei; Liou, Juin J.
ABSTRACT: Different ferroelectric thin films and their related Metal-Semiconductor-Insulator-Metal (MSIM) structures include zinc oxide (ZnO) are studied, which can be utilized in back-gated ferroelectric field-effect transistors (FETs). The most ideal zinc oxide (ZnO) thin film prepared by sol-gel method are obtained under the pyrolysis temperature of 400°C and the annealing temperature of 600°C. The asymmetric or symmetric current-voltage characteristics of the heterostructures with ZnO are exhibited depending on different ferroelectric materials in them. The curves of drain current versus gate voltage for MSIM-structure FETs are investigated, in which obvious counterclockwise loops and a drain current switching ratio up to two orders of magnitude ate observed due to the modulation effect of remnant polarization on the channel resistance. The results also indicate the positive influences of impurity atom substitution in bismuth ferrite thin film for the MSIM-structure FETs.